Superstructures of chiral nematic microspheres as all-optical switchable distributors of light - Aβhoff, Sarah J. (Sci Rep, 2015)
Light technology is based on generating, detecting and controlling the wavelength, polarization and direction of light. Emerging applications range from electronics and telecommunication to health, defence and security. In particular, data transmission and communication technologies are currently asking for increasingly complex and fast devices, and therefore there is a growing interest in materials that can be used to transmit light and also to control the distribution of light in space and time. Here, we design chiral nematic microspheres whose shape enables them to reflect light of different wavelengths and handedness in all directions. Assembled in organized hexagonal superstructures, these microspheres of well-defined sizes communicate optically with high selectivity for the colour and chirality of light. Importantly, when the microspheres are doped with photo-responsive molecular switches, their chiroptical communication can be tuned, both gradually in wavelength and reversibly in polarization. Since the kinetics of the “on” and “off” switching can be adjusted by molecular engineering of the dopants and because the photonic cross-communication is selective with respect to the chirality of the incoming light, these photo-responsive microspheres show potential for chiroptical all-optical distributors and switches, in which wavelength, chirality and direction of the reflected light can be controlled independently and reversibly.